Chemotherapy-related agranulocytosis as a predictive factor for germline BRCA1 pathogenic variants in breast cancer patients: a retrospective cohort study - Noémie Lang; Aurélie Ayme; Chang Ming; Jean‑Damien Combes; Victor N. Chappuis; Alex Friedlaender; Aurélie Vuilleumier; José L. Sandoval; Valeria Viassolo; Pierre O. Chappuis; S. Intidhar Labidi-Galy (Swiss Medical Weekly)
BACKGROUND: Carriers of germline pathogenic variants of the BRCA1 gene (gBRCA1) tend to have a higher incidence of haematological toxicity upon exposure to chemotherapy. We hypothesised that the occurrence of agranulocytosis during the first cycle of (neo-)adjuvant chemotherapy (C1) in breast cancer (BC) patients could predict gBRCA1 pathogenic variants.